Strategi Brand Positioning terhadap Brand Awareness Pada Merek Lokal Koto Batu - Mayank Sari, Yulianti (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to analyze brand positioning strategies to enhance brand awarenessof Koto Batu, a local handmade jewelry brand using natural gemstones and pure silver, craftedby local artisans. Using a descriptive qualitative approach through participant observation, indepth interviews, and literature review, the research explores how Koto Batu builds a distinctivebrand identity through healing benefits, ethnic-modern aesthetics, and social value such aswomen's empowerment and environmental awareness. SWOT analysis indicates that Koto Batu’sstrengths lie in product differentiation, emotional value, and unique design, but challengesremain in limited digital exposure and weak visual identity. Opportunities arise from thegrowing trends of wellness, while threats come from emerging local competitors with similarpositioning. A strong and consistent brand positioning strategy can reinforce brand perception,improve consumer awareness, and expand Koto Batu’s market reach.